Angel Rama: the influence of the the first meeting of peruvian writers on his work - Simon da Silva, Regina (2020)
This article analyzes the dialogue between the Peruvian narrators and critics at the “Primer Encuentro de Narradores Peruanos”, in 1965, in Arequipa, Peru, on writing techniques employed by them, and the influence that these discussions provided for the development of Angel Rama’s work, mainly in his theory of transculturation in his book called Transculturación narrativa en América Latina, (1982). We consider this meeting very important for the formation of Latin American critical thinking and the development of JALLA, which began as Andean studies and nowadays it is a large Latin American congress in the broadest sense of the term.